2019
DOI: 10.1016/j.jclepro.2018.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evaluation of by-products of the grape industry as potential agricultural fertilizers

Abstract: The grape industry, specifically the wine industry, is generating by-products rich in nutrients, which are underutilized and often end up being polluters of the environment. These byproducts are the bagasse, the stem and the grape seed in a proportion of 20% of the grape industrialized, that is, more than 100,000 tons/year in the Serra Gaucha. The use of winemaking by-products in the production of raw materials is a pioneering activity in Brazil and possibly in the world. This study is a characterization of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 16 publications
1
22
0
2
Order By: Relevance
“…According to previous reports, the total output of grapes in the world reached 22.53 million tons in 2017, and grapes ( Vitis vinifera L.) are the world's largest fruit crop except for oranges (Ferrari et al., 2019). It is suitable for processing into juice or wine owing to its acidity, sugar, and anthocyanins content.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports, the total output of grapes in the world reached 22.53 million tons in 2017, and grapes ( Vitis vinifera L.) are the world's largest fruit crop except for oranges (Ferrari et al., 2019). It is suitable for processing into juice or wine owing to its acidity, sugar, and anthocyanins content.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding chemical fertilizers, some authors have suggested interesting improvement strategies to significantly reduce the environmental impact by replacing them with manure [22] or with natural fertilizers obtained from by-products of other production chains [23,24]. The use of manure, and the total or partial replacement of fertilizer with it, is a traditional approach that is recently back to the fore.…”
Section: Wheat Cultivation and Sustainable Agriculture Innovations And Improvements In Wheat Cultivationmentioning
confidence: 99%
“…Only a few studies have developed an evaluation indicator system of the comprehensive benefits of the wine industry to combat desertification. By combining this with agricultural industry's evaluation indicator system for sustainable development [34,35], we constructed a framework of a system covering all aspects of the wine industry's first-level evaluation indicators: industrial investment, industrial development environment, industrialization development level, economic benefits, social benefits, and ecological benefits.…”
Section: Construction Of An Indicator System Of the Comprehensive Benefitsmentioning
confidence: 99%